Cross‐protection, infection and case fatality rates in wild European rabbits experimentally challenged with different rabbit haemorrhagic disease viruses. Issue 5 (1st April 2022) - Patel, Kandarp K.; Strive, Tanja; Hall, Robyn N.; Mutze, Greg; Page, Bradley; Korcz, Matthew; Booth‐Remmers, Mahalia; Smith, Ina L.; Huang, Nina; Kovaliski, John; Jayasinghe Ellakkala Appuhamilage, Ridma M.J.; Taggart, Patrick L.
Abstract: Rabbit haemorrhagic disease virus 2 (RHDV2) is now the dominant calicivirus circulating in wild rabbit populations in Australia. This study compared the infection and case fatality rates of RHDV2 and two RHDVs in wild rabbits, as well as their ability to overcome immunity to the respective other strains. Wild rabbits were allocated to groups either blindly or based on pre‐screening for RHDV/RHDV2 antibodies at capture. Rabbits were monitored regularly until their death or humane killing at 7 days post infection. Liver and eyeball samples were collected for lagovirus testing and aging rabbits, respectively. At capture, rabbits showed high seroprevalence to RHDV2 but not to RHDV. In RHDV/RHDV2 seronegative rabbits at capture, infection rates were highest in those inoculated with RHDV2 (81.8%, 18 out of 22), followed by K5 (53.8%, seven out of 13) and CZECH (40.0%, two out of five), but these differences were not statistically significant. In rabbits with previous exposure to RHDV2 at capture, infection rates were highest when inoculated with K5 (59.6%, 31 out of 52) followed by CZECH (46.0%, 23 out of 50), with infection rates higher in younger rabbits for both viruses. In RHDV/RHDV2 seronegative rabbits at capture, case fatality rates were highest for those inoculated with K5 (71.4%), followed by RHDV2 (50.0%) and CZECH (50.0%). In rabbits with previous exposure to RHDV2 at capture, case fatality rates were highest in rabbits inoculated with K5 (12.9%) followed by CZECH (8.7%), with no case fatalities following RHDV2 inoculation. Case fatality rates did not differ significantly between inoculums in either serostatus group at capture. Based on multivariable modelling, time to death post RHDV inoculation increased in rabbits with recent RHDV2 exposure compared with seronegative rabbits and with age. The results suggest that RHDV2 may cause higher mortalities than other variants in seronegative rabbit populations but that K5 may be more effective in reducing rabbit populations in an RHDV2‐dominant landscape.